Tanfīdz Barnāmij Al-Lughah Al-‘Arabiyyah Fī Ma’had As-salām Kampar Riau : Baina Al-Ittīshālāt, Wa Al Qiyādah, Wa Al-Isyrāf - Nurul Fadhilah Fakaubun; Nurul Elmira Harmeilinda; Zakiyah Arifa (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2021)
Islamic boarding schools (pesantren) continue to play a significant role in the development of education, including the promotion of Arabic language learning. To enhance students’ Arabic language proficiency, Pondok Pesantren Assalam Kampar has implemented a variety of language development programs supported by effective educational management. This study aims to analyze the implementation of the Arabic language program and identify the management model adopted at Pondok Pesantren Assalam Kampar. This research employed a qualitative descriptive approach, with the researcher serving as the primary research instrument. Data were collected through observations, semi-structured interviews, and document analysis, while data validity was ensured through triangulation. Interviews were conducted with the principal and other relevant stakeholders to explore the management practices underlying the implementation of the Arabic language program, particularly in the areas of communication, leadership, and supervision. The findings reveal that the implementation of the Arabic language program is supported by three key management components. First, communication functions as both an input and an output of the management process and is primarily implemented through a bottom-up communication model that encourages active participation and social interaction among school members. Second, leadership is characterized by a participatory approach in which school leaders actively involve teachers and staff in decision-making to achieve institutional goals. Third, supervision is conducted through a democratic model that emphasizes continuous monitoring, guidance, and collaborative evaluation of program implementation. These management practices contribute to the effective implementation of the Arabic language program and support the development of a sustainable Arabic-speaking environment within the pesantren.